Effect of different drying techniques and packaging materials on garlic (Allium sativum) powder - CHAKRABORTY, SHALINI; KUMAR PATEL, SHIV; KUMAR CHAKRABORTY, SUBIR; NYMA, ROHIT (The Indian Journal of Agricultural Sciences, 2022)
Garlic (Allium sativum L.) powder is a convenience product commonly used in domestic and commercial food preparations. The present study was carried out in 2019–20 at Enthkedi, Bhopal, Madhya Pradesh to demonstrate the effect of different drying techniques, viz. shade drying ( 32oC), S1; oven drying (50ºC, 6–8 h), S2; microwave drying (800W, 4 min), S3; and solar drying (10 h), S4; on (un)treated garlic cloves with respect to quality characteristics of garlic powder. The garlic cloves were blanched in boiling water for 10–15 sec followed by dipping in 0.2% potassiummeta-bisulphite (KMS) for 5 min at room temperature, this was the treated sample (T1). The treated samples and untreated samples (T2) were subjected to different drying techniques followed by evaluation in terms of product recovery, rehydration ratio, cutting strength, colour, titratable acidity and ascorbic acid content. Full factorial completely randomized design was adopted for the experiments. It was observed that across all the responses S1 and S4 did not have any significant (P<0.05) effect, while T1 and T2 rendered significant (P<0.05) difference to the responses. The hardness of shade dried (51.87N) garlic clove was significantly (P<0.05) more than that of microwave dried (32.48N). Dried garlic cloves were evaluated for quality parameters (ascorbic acid, acidity) and overall acceptability which was found best with T1 under S1 condition. Microbiological parameters, viz. total viable fungal colony in different packaging material (LDPE, PE, multilayered) was evaluated for garlic powder stored over a period of 60 and 90 days. Multilayered packaging for T1 sample (S2) garlic powder was found to be the most acceptable and safe.